The influence of the European Union member states on developing the haulage of hazardous cargo in Lithuania - Batarlienė, Nijolė; Jarašūnienė, Aldona; Vasiliauskas, Aidas V. (Transport, 2011)
Technological development inevitably increases the number of hazardous cargo in the European Union. The essential problem of the haulage of hazardous consignment deals with insufficient safety. The topic seems to be relevant due to importance to ensure the safety of carrying hazardous cargo, since while transporting such materials, a certain possibility of a negative impact on nature, people’s health and safety occurs. This article assesses the current situation of the haulage of hazardous cargo in Lithuania and investigates activities of developing the possibilities of the haulage of hazardous cargo in the countries of the European Union (EU). The conduced research on transport organizations in the EU countries helped with evaluating safety remedies and with ensuring the safe haulage of hazardous cargo used by particular organizations as well as suggested the kinds of transport used for transporting hazardous cargo. The study also indicated the most frequently crossed countries and the kinds of information technologies an organization applies in practice so that to guarantee the safety of the haulage of hazardous cargo. First Published Online: 12 Apr 2011